ANALISIS KETAHANAN PANGAN (TINJAUAN KETERSEDIAAN DAN AKSES) DI KABUPATEN OKU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2015)
Availablity of rice function ensures supply of rice to meet the needs of entire population in terms of quality, quantity, adn safety. Whereas access to rice is the ability of households to periodically meet considerable amount of rice, to make it happen in an area influenced by several aspect : physical aspects, economc, and social. Purpose of this study is to analyze the availability of rice and access which was conductted in 12 districts in the county OKU using quantitative descriptive method and analyze of secondary data. Results showed in terms of the availibility of rice there are 8 districts which is a surplus and there are 4 which is a defisit. Whereas in terms of access, there are 6 sub-districts are included in both and 6 sub-districts were included in the districts is not good. Seen from the relative condition of the combined availabilty of rice and accees shows that there are there distriscts glittering in a safe position, 7 sub-distriscs glittering alert position and 1 sub-district in a safe position.